Blended Learning Through the Google Classroom in the â€œNew Normalâ€ Era of the Covid-19 Pandemic: EFL Teachersâ€™ Perception and Challenges - Aniek Endrawati; Tono Suwartono (Proceedings Series on Social Sciences & Humanities, 2023)
This study investigates the application of blended learning using the Google Classroom in EFL teaching and learning in the "new normal" era of the COVID-19 pandemic. The research also examines the teachers' perceptions and the obstacles they encountered while applying the Google Classroom for blended learning. The study is a mixed-method survey. As many as thirty-eight English teachers from 25 schools in the town of Wonosobo, Indonesia, participated in the study. They were recruited on a purposive sampling basis. Close-ended questionnaires and interviews were used to collect the data. The finding has revealed that the teachers' perception of using blended learning through the Google Classroom is 83%, falling into the category "Extremely Effective." This result indicated that the Google Classroom is beneficial for teaching-learning activities and effective for student learning outcome. Students could access the teacher-provided learning resources anytime and from any location. However, utilizing the Google Classroom is not obstacles free, with an average of 78% belonging to a "high" difficulty level. Furthermore, the finding has shown that teaching and learning activities using the Google Classroom continue to confront hurdles such as data quota, internet access, and restrictions imposed by the Google Classroom features.